What the United States Can Learn from the European Commission's Better Regulation Initiative. (September 2015) - Broughel, James
Abstract : In May of 2015, the European Commission released a package outlining the vision for its Better Regulation initiative, a program aimed at improving outcomes of European Union (EU) regulation. The move represents a step forward for regulatory reform in the EU, and signals a potential shift in world leadership roles among countries promoting evidence-based policy. The United States (US), once at the forefront of regulatory science and analysis, may now be lagging behind. If Better Regulation is implemented as its ambitious designers envision, this could signal a new role for the EU in advancing 21 st century policymaking. Better Regulation seeks to improve the EU regulatory process in several ways. The initiative allows for more meaningful citizen and stakeholder participation at all stages of the policymaking process; it seeks to institutionalize the use of economic analysis throughout the lifecycle of a policy; and it sets up a process for reviewing the existing stock of regulations to ensure old rules do not become excessively burdensome or obsolete. All this is done in a manner intended to inform legislators as they periodically review funding levels for new and existing programs.